Recent Progress on Bioinspired Antibacterial Surfaces for Biomedical Application - Xiao Yang; Wei Zhang; Xuezhi Qin; Miaomiao Cui; Yunting Guo; Ting Wang; Kaiqiang Wang; Zhenqiang Shi; Chao Zhang; Wanbo Li; Zuankai Wang (Biomimetics, 2022)
Surface bacterial fouling has become an urgent global challenge that calls for resilient solutions. Despite the effectiveness in combating bacterial invasion, antibiotics are susceptible to causing microbial antibiotic resistance that threatens human health and compromises the medication efficacy. In nature, many organisms have evolved a myriad of surfaces with specific physicochemical properties to combat bacteria in diverse environments, providing important inspirations for implementing bioinspired approaches. This review highlights representative natural antibacterial surfaces and discusses their corresponding mechanisms, including repelling adherent bacteria through tailoring surface wettability and mechanically killing bacteria via engineering surface textures. Following this, we present the recent progress in bioinspired active and passive antibacterial strategies. Finally, the biomedical applications and the prospects of these antibacterial surfaces are discussed.